Role of Organizational Accountability in the Reduction of Social Loafing Behavior in the workplace: An Empirical Study in Al-Sadr General Hospital - Al-Jubouri , Ali Abboodi Neamah; Alabassi, 2Zaid M.; Mohammed, Sanaa Jasim (International Journal of Psychosocial Rehabilitation, 2020)
Senior management is an effective tool for strengthening organizational accountability in public organizations. Implementation to enhance accountability remains unclear in most organizations and includes many complex processes due to the disruption of multiple accountability regulations. This study aims to provide an understanding of how regulatory accountability improves employee accountability, by highlighting key elements of the organization that reduce turmoil, employee dysfunction, and social loafing. This study adopts a qualitative approach to the study of staff groups using a set of regulations imposed by the organization. The data was collected using a questionnaire that included semi-organized and organized interviews and reviews of observations at Al-Sadr General Hospital. The results revealed that the dimensions of organizational accountability that mitigate social loafing are classified into four, namely: informal accountability, official accountability, decision accountability, and process accountability; as the task of official accountability is seen as difficult, and can affect social loafing in a positive way, because group members feel it is necessary to make an effort and contribute to the team's performance, because their contribution is unique and necessary to the group's final outcome, although the participants have been randomly selected. This study contributes, and gives greater insight, into how to deal with social loafing in the accountability relationships that exist in research, by providing many elements of success that reduce the chaos of accountability relationships in public institutions. The study highlights the need to examine more elements, particularly in the organizational context, to help public organizations improve their performance and to enhance accountability in their operations.